2020
DOI: 10.1177/0363546520916473
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Borderline Hip Dysplasia Achieve Clinically Significant Improvement After Arthroscopic Femoroacetabular Impingement Surgery: A Case-Control Study With a Minimum 5-Year Follow-up

Abstract: Background: Hip arthroscopy for the treatment of femoroacetabular impingement syndrome (FAIS) in patients with borderline hip dysplasia (BHD) is becoming a more common practice. However, the literature on achieving meaningful outcomes at midterm follow-up, as well as predictors of these outcomes, is limited. Purpose: To (1) compare the rates of achieving meaningful clinical outcomes between patients with and without BHD and (2) identify the predictors for achieving clinical success among patients with BHD 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…While they identified that moderate to severe dysplasia (LCEA, <15°) was a predictor of clinical failure, patients with BD (LCEA, 15°-25°) demonstrated good long-term survival rates. Furthermore, Beck et al 6 evaluated outcomes of patients with BD undergoing hip arthroscopic surgery for femoroacetabular impingement against a matched control group with normal acetabular coverage at minimum 5-year follow-up and found that rates of achieving clinical success were not statistically significantly different between the groups. This study is among the first to investigate this topic in the athletic population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While they identified that moderate to severe dysplasia (LCEA, <15°) was a predictor of clinical failure, patients with BD (LCEA, 15°-25°) demonstrated good long-term survival rates. Furthermore, Beck et al 6 evaluated outcomes of patients with BD undergoing hip arthroscopic surgery for femoroacetabular impingement against a matched control group with normal acetabular coverage at minimum 5-year follow-up and found that rates of achieving clinical success were not statistically significantly different between the groups. This study is among the first to investigate this topic in the athletic population.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated high failure rates, while others have shown favorable outcomes with clinical success rates not significantly different from those in patients with normal acetabular coverage in the general population. 3,6,18,57 In the setting of frank dysplasia (LCEA, <18°), periacetabular osteotomy (PAO) is the preferred treatment; however, a consensus has not been established for the management of patients with BD, who often have a wide spectrum of instability. 43…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 There is increasing evidence that this population of patients may also achieve satisfactory clinical outcomes with arthroscopic treatment. 3,6,7,17,28,43 Increased attention is being paid toward studying hip arthroscopy outcomes in specific patient populations, predominately stratified by age 8,27,62 and sex, 9,47 recognizing that certain demographic subsets of patients have unique pathology and may require differing treatments. In patients with BHD, cohort studies have identified sex-based differences in patient-reported outcome (PRO) measures, with females achieving greater relative improvement of PRO scores after surgery.…”
mentioning
confidence: 99%
“…2 Current mid-term data suggest an index surgery failure rate (of revision arthroscopy or conversion to THA) ranging from 0% to 86%, suggesting that indications for surgery need further optimization. [12][13][14][15] Also, this range of failure rates suggests there is significant variability in the published cohorts to date. 2,[6][7][8][9][10][11][12] Furthermore, only 2 mid-term studies have evaluated minimal clinically important difference (MCID) and patient acceptable symptomatic state (PASS) rates, albeit in an elderly patient cohort older than age 50 years and a strictly microfracture cohort, respectively.…”
mentioning
confidence: 99%